Pericardiectomy for Constrictive Pericarditis with or without Cardiopulmonary Bypass - Huang JB; Tang YT (Vascular Health and Risk Management, 2024)
Jing-Bin Huang, Yun-Tian Tang Department of Cardiothoracic Surgery, The People’s Hospital of Guangxi Zhuang Autonomous Region, and Guangxi Academy of Medical Sciences, Nanning, Guangxi, People’s Republic of ChinaCorrespondence: Jing-Bin Huang; Yun-Tian Tang, Tel +86-771-2188205, Fax +86-771-2188214, Email hjb010222@163.com; liangdaxin2023@163.comAim: We aim to access the effect of pericardiectomy for constrictive pericarditis with or without cardiopulmonary bypass.Methods: This was a review of pericardiectomy for constrictive pericarditis.Results: Cardiopulmonary bypass is actually an important maneuver to attain complete relief of the constriction. The short additional time of cardiopulmonary bypass during the procedure has very little effect on the risk of morbidity of the main operation.Conclusion: Incomplete pericardiectomy perhaps was the cause of postoperative remnant constriction and high diastolic filling pressure leading to multiorgan failure. Complete pericardiectomy (removal of phrenic-to-phrenic and the postero-lateral and inferior wall pericardial thickening) using cardiopulmonary bypass should be the routine for total relief of the constriction of the heart.Keywords: pericardiectomy, constrictive pericarditis, cardiopulmonary bypass